Mechanical tuning of conductance and thermopower in helicene molecular junctions - Vacek, Jaroslav; Chocholoušová, Jana Vacek; Stará, Irena G; Starý, Ivo; Dubi, Yonatan (Nanoscale, 2015)
Helicenes are inherently chiral polyaromatic molecules composed of all-ortho fused benzene rings possessing a spring-like structure. Here, using a combination of density functional theory and tight-binding calculations, it is demonstrated that controlling the length of the helicene molecule by mechanically stretching or compressing the molecular junction can dramatically change the electronic properties of the helicene, leading to a tunable switching behavior of the conductance and thermopower of the junction with on/off ratios of several orders of magnitude. Furthermore, control over the helicene length and number of rings is shown to lead to more than an order of magnitude increase in the thermopower and thermoelectric figure-of-merit over typical molecular junctions, presenting new possibilities of making efficient thermoelectric molecular devices. The physical origin of the strong dependence of the transport properties of the junction is investigated, and found to be related to a shift in the position of the molecular orbitals.